ROLE OF NITRIC OXIDE (NO) IN CAPSAICIN MEDIATED ANTI-PLATELET ACTIVITY IN IN VITRO, IN VIVO, EX-VIVO MODEL OF PLATELET AGGREGATION ASSAY AND ARTERIAL THROMBOSIS IN RAT: POTENTIAL THERAPEUTIC TARGET? - Patel, Mihir K.; Chaudagar, Kiranj K.; Mehta, Anita A. (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: Although recent advances in the treatment of congestive heart disease, mortality among patients' remains a questionable remark. Therefore, we evaluated the role of capsaicin on in vitro and ex vivo platelet aggregation induced by Adenosine Di-Phosphate (ADP) as well as in in vivo thrombosis models and role of NO, KATP was also identified in the capsaicin-induced anti-platelet animal model as well as in vivo model of arterial thrombosis. Methods: According to body weight wistar rats were divided into five groups. Group I and Group II was treated with saline and capsaicin (3 mg/kg, i. v), while animals from Group III were treated with N(ω)-nitro-L-arginine methyl ester (L-NAME) (30 mg/kg, i. v) 30 min before administration of capsaicin (3 mg/kg, i. v). Group IV animals were treated with glibenclamide (10 mg/kg,i. v) 30 min before administration of capsaicin (3 mg/kg, i. v). Group V was considered as a positive control and administered clopidogrel (30 mg/kg, p. o). Animals were subjected for in vitro, ex-vivo platelet aggregation assay. ADP (30µM) was utilized as an aggregating agent in these experiments. After these assays; animals of each group were subjected for subaqueous tail bleeding time in a rat model and FeCl3-induced arterial thrombosis model in rats. Results: In ADP-induced in vitro platelet aggregation, a significant reduction in % platelet aggregation was observed at 50µM (64.35±4.641) and 100µM (52.72±4.192) concentration of capsaicin as compared to vehicle control (85.82±3.716). Capsaicin (3 mg/kg, i. v) also showed a significant reduction (49.53±4.075) in ex-vivo ADP-induced platelet aggregation as compared to vehicle control (89.38±2.057). In FeCl3 induced arterial thrombosis model, Capsaicin (3 mg/kg, i. v) exhibited an increase in time to occlusion in this rodent model and presence of the L-NAME and glibenclamide had inhibited the activity of capsaicin. Conclusion: In our study, capsaicin (50 µM, 100µM) exhibited potent anti-platelet activity in ADP-induced platelet aggregation, similarly capsaicin exhibited significant anti-platelet action in the ex-vivo study. Moreover, the presence of L-NAME and glibenclamide inhibited the anti-thrombotic and anti-platelet action of capsaicin. Therefore, it was concluded that NO and KATP may be involved in the anti-thrombotic action of capsaicin.